Time-varying channel estimation in OFDM systems based on multiple symbols BEM - Yong DING; Shan OUYANG; Yue-lei XIE; Jun-zheng JIANG; Xiao-mao CHEN (Tongxin xuebao)
In view of the problem of low frequency spectrum utilization for the time-varying channel estimation in orthogonal frequency division multiplexing(OFDM) systems based on basis expansion model (BEM),a new method based on multiple symbols BEM was proposed.Compared with the conventional method based on single symbol,the proposed method reduced the subcarriers for pilots.And by means of the baseline tilting technique,the new method mitigated the Gibbs phenomenon caused by Fourier series expansion.The theoretical analysis reveals that the channel model error is reduced due to the introduction of the baseline tilting technique when the normalized Doppler frequency is no more than 1 2 − 1 M 1+ N g N <mtext> </mtext>.Finally,the numerical simulation shows that compared with conventional methods,the proposed algorithm achieves significant improvement on the estimation error performance and bit error rate (BER) performance under the conditions of the corresponding time-varying channel.